Astaxanthin Ameliorates Atopic Dermatitis by Inhibiting the Expression of Signal Molecule NF-kB and Inflammatory Genes in Mice - Donghwan Kim; Yong-Suk Kim; Ho Sueb Song (MEDrang Inc., 2022)
Background This study was conducted to determine the anti-inflammatory effect of astaxanthin, on atopic dermatitis. Methods Changes in mouse body weight, lymph node weight, and the degree of improvement in symptoms were measured to determine the inflammatory response. Real-time reverse transcription-polymerase chain reaction tests were performed to determine the degree of expression of inflammation-related cytokines (IL-31 and IL-33 and chemokines such as CCL17 and CCL22), and western blot analysis was performed to evaluate the expression of inflammation-related factors (iNOS, COX-2, and NF-kB signaling molecules p-IkBα, p50, p-65 and pSTAT3). Results The degree of symptoms significantly improved in the PA+AX group. Lymph node weight in the PA+AX group was lower than the PA group. Inflammatory cytokines (IL-31, IL-33, and inflammatory chemokines such as CCL17 and CCL22) were significantly reduced in the PA+AX group compared with the PA group. The expression of inflammatory genes (iNOS, COX-2, NF-kB and signaling molecules (p-IkBα, p50, p65, and p-STAT 3) was lower in the PA+AX group compared with the PA group. Conclusion Astaxanthin may modulate the inflammatory response in a mouse model of atopic dermatitis and has an anti-inflammatory effect.